Rectal Diclofenac versus High-Dose Rectal Acetaminophen in Children: a randomized clinical trial - Houman Hashemian; Marzie Fallah Khodadoost (Babol University of Medical Sciences, 2021)
Background: Fever is the most common complaint among the children admitted to health care centers. The aim of this study was to compare the anti-pyretic effect of diclofenac and high dose acetaminophen suppository in 1 to 6 years old children. Methods: This double-blind clinical trial study was performed on 1-6-year-old children hospitalized in 17th Shahrivar Teaching Hospital, Rasht, Iran. Children were divided into two groups of 45 using a block randomization design. The first group received a high dose of acetaminophen suppository at a dose of 30 mg/kg and the second group received a diclofenac suppository at a dose of 1 mg/kg. The rectal temperature of the patients was measured using a digital thermometer at the time of drug administration, and one and three hours after that. Results: 90 children were studied in two groups of 45 each. Temperature changes in the diclofenac group were significantly greater than the acetaminophen group, so from zero to 3 hours after administering diclofenac, the temperature decreased to 1.76±0.95°C. This reduction was lower in acetaminophen group (1.26±0.49°C, P=0.019). Conclusion: Both acetaminophen and diclofenac suppositories significantly reduced the rectal temperature. However, the effect of rectal diclofenac on reducing temperature is more than rectal acetaminophen.